Pattern of Immunophenotype Among the Cases of Lymphoma Attending in A Tertiary Level Hospital - Munira, Shirajam; Afroze, Salama; Biswas, Akhil Ranjon; Khan, MA (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background : To explore the relative frequency and different forms of lymphoma in tertiary level hospital. Methods: This descriptive observational study was carried out in the Department of Hematology at Dhaka Medical College Hospital, Dhaka. Patients attended with solid tissue lymphoma in Outpatient, Inpatient and Lymphoma Clinic services of Department of Hematology and Bone Marrow Transplant, Dhaka Medical College Hospital, Dhaka were taken as study population as per inclusion criteria. A total of 63 patients with lymphoma diagnosed by histopathologically were selected initially, among them 53 were confirmed by immunohistochemistry taken as study population finally. Results: Mean age was 39.2 ± 15.5 years, median age was 36 years within the range of 14 – 75 years. Males were predominant. Male female ratio was 4.3:1. Most of the samples were collected from cervical lymph node (84.1%). Most of the patients came with fatigue and significant weight loss. Maximum 42 (79.24%) cases were Non-Hodgkin’s lymphoma and 11 (20.75%) cases were Hodgkin’s lymphoma. Out of 42 non-Hodgkin’s lymphoma, 27 (64.3%) were B-cell lymphoma and 15 (35.7%) were T-cell lymphoma. Among B-cell lymphoma, 19 (45.2%) were diffuse large B cell lymphoma, three (7.1%) were follicular lymphoma, three (7.1%) were mantle cell lymphoma, one (2.4%) was spleenic marginal zone lymphoma and one (2.4%) was Burkitt lymphoma. Among T-cell lymphoma, nine (21.4%) were peripheral T-cell lymphoma and six (14.3%) were adult T lymphoblastic lymphoma. Out of 11 Hodgkin’s lymphoma, 10 (90.9%) were classical Hodgkin’s lymphoma and one (9.1%) nodular lymphocyte predominant. Among classical Hodgkin’s lymphoma, five (45.5%) were mixed cellularity, three (27.3%) were lymphocyte predominant and two (18.2%) were Nodular sclerosis. Out of 42 non-Hodgkin’s lymphoma, 13 (30.95%) were indolent, 21 (50.00%) were aggressive and eight (19.05%) were very aggressive. Conclusion: In our study, it was found that 79.3% were non-Hodgkin lymphoma of which 64.3% were B-cell lymphoma & 35.7% were T-cell lymphoma and 20.7% cases were Hodgkin lymphoma of which 90.9% were classical Hodgkin’s lymphoma, 9.1% nodular lymphocyte predominant Hodgkin’s lymphoma. Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 21-25